Factorisation using common factors

Factorization by common factors

Ex 12.1, 1 (i)

Ex 12.1, 1 (ii)

Ex 12.1, 1 (iii) Important

Ex 12.1, 1 (iv) Important

Ex 12.1, 1 (v)

Ex 12.1, 1 (vi) Important

Ex 12.1, 1 (vii)

Ex 12.1, 1 (viii) Important

Example 2 Important

Example 1

Ex 12.1, 2 (i)

Ex 12.1, 2 (ii) Important

Ex 12.1, 2 (iii)

Ex 12.1, 2 (iv) Important You are here

Ex 12.1, 2 (v)

Ex 12.1, 2 (vi)

Ex 12.1, 2 (vii)

Ex 12.1, 2 (viii) Important

Ex 12.1, 2 (ix)

Ex 12.1, 2 (x) Important

Last updated at April 16, 2024 by Teachoo

Ex 12.1, 2 (Method 1) Factorise the following expressions. (iv) – 16z + 20 𝑧^3− 16z + 20𝑧^3 = (4 × −4) z + (4 × 5)𝑧^3 Taking 4 common, = 4 (−4z + 5𝑧^3) = 4 (−4 × z + 5𝑧^2 × z) Taking z common, = 4 × z (−4 + 5𝑧^2) = 4z (−4 + 5𝒛^𝟐) Ex 12.1, 2 (Method 2) Factorise the following expressions. (iv) – 16z + 20 𝑧^3−16z = −16 × z = −1 × 16 × z = −1 × 2 × 2 × 2 × 2 × z 20𝒛^𝟑 = 20 × 𝑧^3 = 2 × 2 × 5 × z × z × z So, 2, 2 and z are the common factors. Now −16z +20𝑧^3 = (−1 × 2 × 2 × 2 × z) + (2 × 2 × 5 × z × z × z) Talking 2 × 2 × z common, = 2 × 2 × z ((−1 × 2 × 2) + (5 × z × z)) = 4z (−4 + 5𝒛^𝟐)